Emerging Infectious Diseases, Antimicrobial Resistance and Millennium Development Goals: Resolving the Challenges through One Health - G. V. Asokan; R. K. Kasimanickam (University Library System, University of Pittsburgh, 2014)
Most emerging infectious diseases are zoonoses, which could severely hamper reaching the targets of millennium development goals (MDG). Five out of the total eight MDG's are strongly associated with the Emerging Infectious Diseases (EIDs). Recent emergence and dissemination of drug-resistant pathogens has accelerated and prevent reaching the targets of MDG, with shrinking of therapeutic arsenal, mostly due to antimicrobial resistance (AMR). World Health Organization (WHO has identified AMR as 1 of the 3 greatest threats to global health. Until now, methicillin-resistant staphylococcus aureus (MRSA) and vancomycin-resistant enterococci (VRE) have been observed in hospital-acquired infections. In India, within a span of three years, New Delhi metallo-β-lactamase prevalence has risen from three percent in hospitals to twenty- fifty percent and is found to be colistin resistant as well. Routine use of antimicrobials in animal husbandry accounts for more than 50% in tonnage of all antimicrobial production to promote growth and prophylaxis. This has consequences to human health and environmental contamination with a profound impact on the environmental microbiome, resulting in resistance. Antibiotic development is now considered a global health crisis. The average time required to receive regulatory approval is 7.2 years. Moreover, the clinical approval success is only 16%. To overcome resistance in antimicrobials, intersectoral partnerships among medical, veterinary, and environmental disciplines, with specific epidemiological, diagnostic, and therapeutic approaches are needed. Joint efforts under "One Health", beyond individual professional boundaries are required to stop antimicrobial resistance against zoonoses (EID) and reach the MDG.